Leigh-like neuroimaging features associated with new biallelic mutations in OPA1. (July 2017) - Rubegni, Anna; Pisano, Tiziana; Bacci, Giacomo; Tessa, Alessandra; Battini, Roberta; Procopio, Elena; Giglio, Sabrina; Pasquariello, Rosa; Santorelli, Filippo Maria; Guerrini, Renzo; Nesti, Claudia
Abstract: Behr syndrome is characterized by the association of early onset optic atrophy, cerebellar ataxia, pyramidal signs, peripheral neuropathy and mental retardation. Recently, some cases were reported to be caused by biallelic mutations in OPA1 . We describe an 11-year-old girl (Pt1) and a 7-year-old boy (Pt2) with cognitive delay, ataxic gait and clinical signs suggestive of a peripheral neuropathy, with onset in early infancy. In Pt1 ocular fundus examination revealed optic disk pallor whereas Pt2 exhibited severe optic atrophy. In both children neuroimaging detected a progressive cerebellar involvement accompanied by basal ganglia hyperintensities and pathological peak levels of lactate. In both patients, muscle biopsy showed diffuse reduction of cytochrome c oxidase stain, some atrophic fibers and type II fiber grouping. Using a targeted resequencing panel in next generation sequencing, we identified the homozygous c.1180G>A/p.Ala394Thr mutation in Pt1 and the c.2779-2A>C mutation in compound heterozygosity with the c.2809C>T/p.Arg937Cys mutation in Pt2. All variants were novel and segregated in the healthy parents. Expression of OPA1 protein was significantly reduced in muscle tissues of both patients by Western blotting. We also observed in patients' fibroblasts a higher proportion of fragmented and intermediate mitochondria upon galactose treatment compared to controls, as already seen in other patients harboring mutations in OPA1 . The presence of Leigh-like neuroimaging features is a novel finding in Behr syndrome and further adds to the complex genotype–phenotype correlations in OPA1 -associated disorders.